A problemática do licenciamento ambiental em zona de amortecimento de unidades de conservação - Andre de Lima Andrade (2005)
This dissertation assesses the environmental licensing procedures of potentially polluting activities in buffer zones of protected areas, also known as ZAUC . The main problems of the current procedures had been identified, from questionnaires sent to the heads of national parks, from an assessment of selected licensing processes at the Brazilian Institute for Environment, IBAMA, and from a case study made at Serra do Cipo National Park. Some possible solutions to those problems are also discussed. It was concluded that the current procedure for environmental licensing, applied to the activities located in ZAUC has many problems: the legislation which governs the procedure is vague and outdated , participation by the local residents is not encourgaged, there is noclear definition of which economic activities should be subjected to environmental licensing or which documentation, studies and projects are necessary to proceed with the assessment. In addition, the government branch which should be licensing those activities are not well established. However, the data obtained in this research show that 97% of the parks included in this assessment suffer impacts as a result of economic activities performed in the neighboring buffer zones, which are not being considered in the licensing procedures, especially the ones which have low pollutant impact. This situation was made clear in the case study made at Serra do Cipo National Park where entrepreneurs subdivide land and construct inns without any environmental control. With the aim of improving the situation and the procedures of environmental licensing of economic activities located in the buffer zones, a change in the CONAMA 013/90 resolution, which rules the environmental licensing of those areas, is proposed.Some concepts like the existence of buffer zones, general mangement plans of the area and consultant boards with participants of local society were included.A simplified licensing procedure, appropriate for activities of small sollution potential and also more suitable to the Brazilian reality is also suggested.